Pemberdayaan Masyarakat Melalui Kegiatan Apikultur di Desa Baseh Kedungbanteng Kabupaten Banyumass di Desa Baseh Kedungbanteng Kabupaten Banyumas - Herliana, Okti (LPPM Universitas Trunojoyo Madura, 2023)
Baseh Village, Banyumas Regency is one of the villages located at the foot of Mount Slamet and directly adjacent to the forest. The richness of nature and diverse vegetation conditions make it a suitable place to cultivate bees. However, this potential has not been utilized optimally. Therefore, it is hoped that the Dissemination and Transfer of Honey Bee Cultivation Technology activities will be a solution. The implementation method is through Participatory Rural Appraisal (PRA). The implementation of this activity targets LMDH and Karang Taruna in Baseh Village, by providing technical guidance. Apiculture is the cultivation of honey bees carried out in forestry activities or components. The first thing that must be done is to observe and assess the availability of existing resources. The bees that are cultivated are Apis cerana and Apis Trigona leaviceps. This activity is expected to be able to support sustainable agroforestry and agricultural systems in Baseh Village and become a source of income for the target group to realize SDG's in Baseh Village.